Cytotoxicity Effects of Zanthoxylum simulans Hance. Fruit Bark Extract - Thuy Tien, Dang; Thị Thuy, Nguyen; Manh Ha, Vu; Thanh Tung, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2023)
Zanthoxylum simulans Hance. is known in folklore as a spicy herb, commonly used to treat cold-induced diseases in the body. In this study, we evaluated the cytotoxic effects of Zanthoxylum simulans fruit bark extract. Samples of Zanthoxylum simulans were extracted with 70% ethanol and subsequently fractionated with n-Hexane, ethyl acetate (EtOAc), and n-butanol (n-BuOH) solvents. To evaluate the cytotoxic effect, we performed SRB (Sulforhodamine B) assay on the three cell lines human liver HepG2, lung SK-LU-1, and cervical carcinoma Hela. The results showed that the EtOH total extract had the strongest cytotoxicity effects on liver cancer cells with an IC 50 of 63.68±3.97 mg/mL, but showed no toxicity to SK-LU-1 lung cancer or Hela cervical cancer cells. The results of cytotoxic effects on HepG2 liver cancer cells of these fractions showed that the n-Hexane and EtOAc fractions exhibited activity with IC 50 values of 17.12±0.94 and 28.45±2.85 µg/mL, respectively, while the n-BuOH and H 2 O fractions showed no activity. Our results showed that Zanthoxylum simulans fruit bark extract has a strong cytotoxicity effect on liver cancer cells.